ANALISIS PEMAHAMAN SISWA KELAS V TERHADAP MITIGASI BENCANA BANJIR DI SEKOLAH DASAR NEGERI 006 LIMAU MANIS AIRTIRIS - Ayuni Wahyu Ilahi; Eddy Noviana; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to describe how grade V students' understanding of flood disaster mitigation at 006 Limau Manis Airtiris Public Elementary School. The data used in this research is primary data obtained directly from data sources. Data analysis is an activity after data from all respondents or other data sources has been collected, data analysis activities are grouping data based on variables and types of respondents, tabulating data based on variables and types of respondents, presenting each variable studied, performing calculations to test the hypotheses that have been proposed. The results of the research on the understanding of fifth grade students on flood disaster mitigation at the 006 Limau Manis Airtiris Public Elementary School are well classified in the understanding category. This can be proven by using data analysis of fifth grade students' understanding of flood disaster mitigation at 006 Limau Manis Airtiris Public Elementary School.Key Words: Student understanding, Flood disaster mitigation